Intellectual Property Rights and Competition: A Framework for the Analysis of Economic and Legal Issues - Gallini, Nancy; Trebilcock, Michael (Competition Policy and Intellectual Property Rights in the Knowledge-Based Economy, 1998)
This is the version of record of a chapter authored by Nancy Gallini and Michael Trebilcock, and published by the University of Calgary Press.
Keywords: Competition Policy; Economic Literature Review; Intellectual property

Statutory civil remedies in trade mark litigation - Kelbrick, Roshana (University of South Africa, 1997)
Little attention is paid to the civil remedies available when infringement of a trade mark or the right to goodwill occurs. Yet, for the owners of ~uch rights, these remedies are of much greater importance than theoretical considerations regarding the nature of the rights or what constitutes their infringement. This thesis analyses the civil remedies for trade mark infringement granted by the South African Trade Marks Act 194 of 1993. In the South African context, any consideration of civil remedies is rendered problematic by the attempted graft of English remedies onto a legal system with a different common-law background. It is, therefore, essential first to trace the English origin and application of these remedies, and then to determine whether each remedy is acceptable in terms of the South African common law. This is necessary, as our courts have previously rejected or adapted English remedies which were unknown to our common law but which Parliament introduced in legislation. The remedies of interdict (or injunction) in final and interlocutory form, compensatory damages, reasonable royalties, and delivery up are analysed from a substantive law and a procedural perspective. The procedural innovation of an inquiry as to damages is also considered. In respect of each remedy, (1) the English roots and development of the remedy are traced; (2) differences of approach in two other Commonwealth jurisdictions, Australia and Canada, are highlighted; (3) the development of the South African equivalent is detailed; and (4) suggestions for the future implementation of the remedy in South Africa are made. In the penultimate chapter, our common law and legislation (including the Constitution of the Republic of South Africa 108 of 1996 ) are measured against the requirements of the Agreement on Trade-related Aspects of Intellectual Property Rights (TRIPS). Recommendations for the effective utilization of each remedy in South Africa are then made. They include suggestions for legislative amendment in respect of delivery up and an inquiry as to damages, and the introduction of statutory damages as an further civil remedy.
Keywords: Civil remedy; Intellectual property; Trade marks; Trademark dispute; Trademark litigation